Оценка изменения характеристик микрорайонной тепловой сети при переходе к двухтрубной системе теплоснабжения с учетом возможного утепления зданий - Алексахин, Александр Алексеевич; Бобловский, Александр Владимирович (Український державний університет залізничного транспорту, 2015)
На примере групп зданий с одинаковыми тепловыми загрузками, но разными характеристиками застройки проанализировано изменение тепловых потерь трубопроводами водяной системы теплоснабжения и расхода электроэнергии для транспортирования воды по территории микрорайона при переходе от четырехтрубной схемы организации теплоснабжения к двухтрубной с учетом возможного утепления зданий. Полученные результаты могут быть полезны при разработке стратегии реформирования микрорайонной системы теплоснабжения.

On the example of an idealized group of residential buildings with the same teplovye downloads, but different characteristics of development the analysis of changes in Teplova loss water pipelines of heat supply system and conditional energy consumption for transportation of water by the district when replacing four pipe schemes of double-pipe heat supply. This transition provides a significant reduction of heat losses in networks. It is shown that the preliminary insulation of buildings, reducing the need for mains water for heating buildings, in some cases to perform this transition with the use of existing neighborhood heat network without their reconstruction. The magnitude of change neighborhood indicators systems heating depends on the thermal parameters of the network (length, diameter, method of laying,characteristic of the thermal insulation of pipelines), constructive features and the number of storeys of buildings. The results obtained can be useful in developing the strategy of reforming the micro-district heating system.
Evaluation of changes in the neighborhood characteristics of the heat network during the transition to two-pipe heating system with the possibility of thermal insulation of buildings
Keywords: централизованное теплоснабжение; тепловые сети; тепловые потери; энергосбережение; утепление зданий; district heating; micro-district heating networks; heat loss; energy saving; thermal insulation of buildings